2020
DOI: 10.21203/rs.2.24838/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for postoperative delirium in patients with triple-branched stent graft implantation

Abstract: Background: Neurological complications is a common complication following novel triple-branched stent graft implantation in patients with Stanford type A aortic dissection (AAD). But the incidence and risk factors of postoperative delirium (POD) are not completely clear. The aim of this study was to investigate the incidence and risk factors of POD after novel triple-branched stent graft implantation.Methods: An observational study of AAD patients who underwent novel triple-branched stent graft implantation be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The inclusion criteria were as follows: (1) age > 18 years, (2) documented permission to participate in the research. The exclusion criteria were as follows: (1) history of neurological or psychiatric disorders such as dementia, stroke, schizophrenia, and depression, (2) diagnosis of liver cirrhosis and uremia, (3) suffered from stroke or brain malperfusion prior to MTBSG, (4) suffered from cardiac tamponade-induced presurgical shock or hemodynamic instability, (5) levels of liver enzymes over four times those of baseline, (6) impaired hearing and/or vision, (7) patients who fell into coma after MTBSG, or who died < 24 h of MTBSG, (8) those who received extracorporeal membrane oxygenation therapy.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were as follows: (1) age > 18 years, (2) documented permission to participate in the research. The exclusion criteria were as follows: (1) history of neurological or psychiatric disorders such as dementia, stroke, schizophrenia, and depression, (2) diagnosis of liver cirrhosis and uremia, (3) suffered from stroke or brain malperfusion prior to MTBSG, (4) suffered from cardiac tamponade-induced presurgical shock or hemodynamic instability, (5) levels of liver enzymes over four times those of baseline, (6) impaired hearing and/or vision, (7) patients who fell into coma after MTBSG, or who died < 24 h of MTBSG, (8) those who received extracorporeal membrane oxygenation therapy.…”
Section: Study Populationmentioning
confidence: 99%
“…Previously, we observed a POD incidence of 37.86% following MTBSG [8]. Among the stand-alone RFs of POD were an acute physiology and chronic health evaluation II (APACHE-II) score > 20, hypoxemia, and other forms of analgesics and sedatives [8]. However, there is limited information on the long-term survival of AAD patients who developed POD after MTBSG.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of acute Stanford type A AD received various surgical treatments, including fenestration, parallel grafting, and branched stent grafting 8 . However, high incidence of postoperative complications continues to be reported 9 . It remains controversial on the optimal surgical intervention of Stanford type A AD.…”
Section: Introductionmentioning
confidence: 99%
“…TBSG implantation was first described by Chen et al 3 in 2010 and is effective in the treatment of type A aortic dissections, however, the procedure, as with most cardiac surgeries is not without risk. Risks associated with this technique include occlusion and disruption of the aorta, paraplegia, and hypoxemia 4,5 …”
mentioning
confidence: 99%
“…This is evidenced in a retrospective single‐center study by Wang et al 13 which highlighted the fact that 12.2%−27% of patients undergoing cardiopulmonary bypass experienced postoperative hypoxemia. Failure to consider the neurological status of patients further limits the study, as an observational study by Lin et al 5 concluded that hypoxemia following the insertion of a TBSG increases the risk of postoperative delirium, calling to attention its significance. Still, as mentioned by Wang et al, 6 there exists a scarcity of studies assessing the risk factors of postoperative hypoxemia after TBSG implantation.…”
mentioning
confidence: 99%